Proceedings of the 1st ACM SIGCAS Conference on Computing and Sustainable Societies 2018
DOI: 10.1145/3209811.3209817
|View full text |Cite
|
Sign up to set email alerts
|

ThinSIM-based Attacks on Mobile Money Systems

Abstract: Phone-based mobile money is becoming the dominant paradigm for financial services in the developing world. For example, mPesa has a cash flow of over thirty billion USD, equivalent to nearly half of Kenya's GDP. Inside of these markets, competitors have appeared who leverage ThinSIMS, small SIM-card add-ons, to provide alternative mobile money implementations. However, the security implications of ThinSIMs are not well understood. To resolve this, we explore the security of phone-based mobile money systems aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…However, to date, there are no strong security controls to suit all mobile money authentication security challenges. However, the existing proposed algorithms, though promising, require more work because they are vulnerable to impersonation attacks; USSD technology vulnerabilities; replay attacks; spoofing attacks; Trojan horse attacks; bruteforce attacks; shoulder-surfing attacks; MITM attacks; insider attacks; identity theft; social engineering attacks; SIM-swapping attacks; malware attacks; agent-driven fraud; and privacy attacks [8,9,11,[22][23][24][25][26]. Therefore, there is a need to develop a secure and efficient multi-factor authentication algorithm for mobile money applications where mobile money subscribers are authenticated using a PIN, OTP, and biometric fingerprints.…”
Section: Problem Statementmentioning
confidence: 99%
“…However, to date, there are no strong security controls to suit all mobile money authentication security challenges. However, the existing proposed algorithms, though promising, require more work because they are vulnerable to impersonation attacks; USSD technology vulnerabilities; replay attacks; spoofing attacks; Trojan horse attacks; bruteforce attacks; shoulder-surfing attacks; MITM attacks; insider attacks; identity theft; social engineering attacks; SIM-swapping attacks; malware attacks; agent-driven fraud; and privacy attacks [8,9,11,[22][23][24][25][26]. Therefore, there is a need to develop a secure and efficient multi-factor authentication algorithm for mobile money applications where mobile money subscribers are authenticated using a PIN, OTP, and biometric fingerprints.…”
Section: Problem Statementmentioning
confidence: 99%
“…Likewise, the adversary can use a BTS with the same mobile network code as the subscriber's real network to perform a MITM attack since the network authenticates users [26,43,45]. Furthermore, the information carried within the communication channel is in plaintext, thus making USSD data vulnerable to attack and redirection [20,21,52]. Salami attack: This is where an employee of a financial institution installs a malware like a Trojan horse on the server hosting the application to withdraw a small amount of money from the subscribers' accounts and deposit it into their account.…”
Section: Attacks Against Integritymentioning
confidence: 99%
“…Despite the considerable effort invested in providing a more robust and secure system, most of the existing MMSs still rely on a weak two-factor authentication (2FA) scheme. Various attacks to mobile money's 2FA scheme include man-in-the-middle (MITM) attack, authentication attack, replay attack, identity theft, USSD technology vulnerabilities, brute force attack, social engineering attacks, and denial of service (DoS) attack [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Reaves et al [23] also observed that the current MMS uses nonstandard cryptography, which is easily compromised, thus limiting the integrity and privacy guarantees of the software, giving rise to the threat of forged transactions and loss of transaction privacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ibtasam [ 18 ] explored the usability and learnability of smartphone mobile wallet applications. Vulnerability of mobile money through “thin-sim” attacks is explored by Phipps [ 32 ]. The problem of security of mobile apps is evaluated by Reaves [ 33 ], and later by Castle [ 5 ].…”
Section: Related Workmentioning
confidence: 99%